Genomes-based phylogeny of the genus Xanthomonas (2012)
Background The genus Xanthomonas comprises several plant pathogenic bacteria affecting a wide range of hosts. Despite the economic, industrial and biological importance of Xanthomonas, the classification and phylogenetic relationships within the genus are still under active debate. Some of the relationships between pathovars and species have not been thoroughly clarified, with old pathovars becoming new species. A change in the genus name has been recently suggested for Xanthomonas albilineans, an early branching species currently located in this genus, but a thorough phylogenomic reconstruction would aid in solving these and other discrepancies in this genus. Results Here we report the results of the genome-wide analysis of DNA sequences from 989 orthologous groups from 17 Xanthomonas spp. genomes available to date, representing all major lineages within the genus. The phylogenetic and computational analyses used in this study have been automated in a Perl package designated Unus, which provides a framework for phylogenomic analyses which can be applied to other datasets at the genomic level. Unus can also be easily incorporated into other phylogenomic pipelines. Conclusions Our phylogeny agrees with previous phylogenetic topologies on the genus, but revealed that the genomes of Xanthomonas citri and Xanthomonas fuscans belong to the same species, and that of Xanthomonas albilineans is basal to the joint clade of Xanthomonas and Xylella fastidiosa. Genome reduction was identified in the species Xanthomonas vasicola in addition to the previously identified reduction in Xanthomonas albilineans. Lateral gene transfer was also observed in two gene clusters.